Legality Of IDK Stablecoin In Legal Perspective In Indonesia - Muhammad Zea Algabili; Siti Mahmudah (Journal of Social Research, 2024)
Stablecoins have emerged as an innovation in the cryptocurrency ecosystem, offering the desired stability of value while maintaining the decentralized characteristics of blockchain technology. One such example is the stablecoin IDK, which claims to provide stable value and wide usage in Indonesia. However, the development of these stablecoins raises important questions about their legality within the Indonesian legal framework. This article aims to analyze the legality of the IDK stablecoin from an Indonesian legal perspective, focusing on regulatory aspects, legal validity, consumer protection and its potential impact on the country's monetary and financial system. This research uses a normative legal analysis method by referring to relevant legislation, the views of financial authorities, and existing legal principles. First, this article will examine the existing regulatory framework in Indonesia regarding cryptocurrencies and digital assets, and its relevance to the IDK stablecoin. Second, we will discuss the legal validity of the IDK stablecoin from a contractual and currency perspective, as well as whether this is in accordance with applicable legal principles. Finally, this article will analyze the potential impact of the use of the IDK stablecoin on the Indonesian monetary and financial system, including implications for monetary policy, financial stability and consumer protection. The results of this study are expected to provide a deeper understanding of whether the IDK stablecoin complies with Indonesian law. The implications of this analysis can provide guidance for regulators, industry players and other related parties in dealing with legal issues that arise along with the development of financial technology. As such, this article can become a foundation for further discussion on stablecoin regulation in the context of Indonesian law.